HAK JAMINAN KESEHATAN ISTRI MENURUT KETENTUAN FIQH TENTANG NAFKAH (Analisis Fiqh Al-SyÄfiâ€™iyyah) - Muhammad Yasir; Fauzal Fikra (SYARIAH: Journal of Islamic Law, 2023)
The purpose of this study was to find out the provisions of Fiqh Al-SyÄfi'iyyah regarding the wife's maintenance and to find out the wife's health security rights according to the provisions of Fiqh Al-SyÄfi'iyyah regarding maintenance. This research is a library researchwith a qualitative type and is descriptive through a normative approach with documentation data collection techniques and content analysis techniques. The results of his research stated that the provisions of Fiqh Al-SyÄfi'iyyah regarding the wife's maintenance are that the husband is obliged to provide maintenance in the form of staple food along with side dishes, clothing and shelter. The obligation of staple food along with side dishes and clothing is adjusted to the condition of the rich, poor or middle husband, while the obligation to live is adjusted to the condition of the wife. The obligation to live is different from the obligation to eat and clothe, because the obligation to live according to the circumstances of the wife is to take advantage of it without ownership, while the obligation to eat and clothe is ownership, where the wife can have a replacement when the husband does not provide it. The wife's right to health insurance according to the provisions of Fiqh Al-SyÄfi'iyyah regarding maintenance is not mandatory. This provision is based on the qiyas (analogy) of a house being rented out. This means that a sick wife is like a rented house in a state of disrepair, and giving medicine to a wife is the same as repairing a house for the needs of the authenticity of the house which is the owner's obligation, so that the medicine is not the obligation of the husband which is the original (bodily) need of the wife which is returned to the parents. wife or himself.